162 Using carcinogenic classifications of pesticides to evaluate the risk of select cancers in Canadian men. (11th October 2013) - Pahwa, M P; Demers,; Kachuri,; Navaranjan,; Blair,; Hohenadel,; Spinelli,; McLaughlin,; Dosman,; Pahwa,; Harris,
Abstract : Objective: To examine possible associations between exposure to pesticides classified by their carcinogenicity and the risk of select cancers in Canadian men. Methods: Between 1991 and 1994, data were collected in six provinces using paper and telephone questionnaires from cases with incident non-Hodgkin lymphoma (NHL) (N = 513), multiple myeloma (MM) (N = 342), soft tissue sarcoma (STS) (N = 357), and Hodgkin lymphoma (HL) (N = 316) and a random, population-based sample of 1506 age- and province-matched controls. Pesticides were grouped into carcinogenic categories using a composite score created from evaluations by the International Agency for Research on Cancer (IARC) and US Environmental Protection Agency (US EPA). Pesticides were categorised as "probably" carcinogenic (IARC Group 2A and/or US EPA Group B and higher) or "possibly" carcinogenic (IARC Group 2B and/or US EPA Group C and higher). Logistic regression was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs). Models were adjusted for age, province, and use of a proxy respondent. Results: Nearly 20 "probably" and 50 "possibly" carcinogenic pesticides were reportedly used by participants. Men who used any "probably" carcinogenic pesticide had increased odds for NHL (OR = 1.63, 95% CI: 1.23−2.16) and MM (OR = 1.56, 95% CI: 1.12−2.18), but not for STS (OR = 1.13; 95% CI: 0.81−1.58) and HL (OR = 0.99, 95% CI: 0.66−1.48) relative to men who did not use these pesticides. Similarly, men who used any "possibly" carcinogenic pesticide had higher odds for NHL (OR = 1.54, 95% CI: 1.21−1.96) and MM (OR = 1.36, 95% CI: 1.02−1.81), but not for STS (OR = 1.02, 95% CI: 0.77−1.35) and HL (OR = 0.97, 95% CI: 0.70−1.33). Conclusions: The use of any carcinogenic pesticide was associated with modest increases in odds for NHL and MM, but not for STS and HD. The ORs were slightly larger from use of "probably" compared to "possibly" carcinogenic pesticides. These results are consistent with IARC and US EPA pesticide classifications.